PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PARTISIPASI KOMITE SEKOLAH TERHADAP KINERJA GURU - Imansyah, M; Arafat, Yasir; Wardiah, Dessy (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This study aimed at determining the effect of school principal leadership and school committee participation on the performance of high school teachers in Muara Enim Regency. This research uses quantitative methods with correlational type of research. The study population of 768 people, namely high school teachers in Muara Enim Regency. The research sample of 263 people. The sampling technique in this study is cluster sampling (area sampling). Data collection techniques using a questionnaire. Data were analyzed using correlation analysis and multiple regression techniques. The results showed that: (1) Principal leadership had a positive and significant effect on the performance of high school teachers in Muara Enim Regency. (2) School committee participation has a positive and significant effect on the performance of high school teachers in Muara Enim Regency; and (3) Principal leadership and school committee participation jointly have a positive and significant effect on the performance of high school teachers in Muara Enim Regency.